Pleistocene speciation of freshwater crabs (Crustacea: Potamidae: Geothelphusa) from northern Taiwan and southern Ryukyus, as revealed by phylogenetic relationships - Shih, H.-T. (2014)
10.1016/j.jcz.2011.07.004